Another functional frame‐shift polymorphism of DEFB126 (rs11467497) associated with male infertility. Issue 5 (27th February 2015) - Duan, Shiwei; Shi, Changgeng; Chen, Guowu; Zheng, Ju‐fen; Wu, Bin; Diao, Hua; Ji, Lindan; Gu, Yihua; Xin, Aijie; Wu, Yancheng; Zhou, Weijin; Miao, Maohua; et al.
Abstract DEFB126 rs140685149 mutation was shown to cause sperm dysfunction and subfertility. Indel rs11467497 is another 4‐nucleotide frame‐shift mutation (151bp upstream of rs140685149) that leads to the premature termination of translation and the expression of peptide truncated at the carboxyl terminus. In the present study, we performed a comprehensive association study to check the contribution of rs140685149 and rs11467497 to male infertility. Our results confirmed the previous findings that there was no association between rs140685149 and sperm motility. In contrast, we found a significant association of another indel rs11467497 with male infertility. Moreover, rs11467497 was shown to be associated with higher number of round cells in the infertile males with low sperm motility. Surprisingly, the two mutations commonly existed in the sperm donors (n = 672), suggesting a potential application of the two indels in the screening for eligible sperm donors. Western blotting assays showed the sperms with rs140685149 2‐nt deletion tended to have unstable DEFB126 protein in contrast of no DEFB126 protein expressed in the sperms with rs11467497 4‐nt deletion, suggesting a more severe consequence caused by rs11467497 mutation. In conclusion, our study presented a significant contribution of another functional frame‐shift polymorphism of DEFB126 (rs11467497) to male infertility.